2021
DOI: 10.3389/fphys.2021.638352
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Target of Rapamycin Signaling Pathway Regulates Mitochondrial Quality Control of Brown Adipocytes in Mice

Abstract: The mammalian target of rapamycin (mTOR) is an important protein kinase that senses changes in extracellular and intracellular energy levels and plays a key role in regulating energy metabolism. Brown adipose tissue, which can be converted to white adipose tissue, contains a large number of mitochondria and regulates energy expenditure through thermogenesis. Because obesity is a process of fat accumulation due to chronic excessive energy intake, we attempted to determine whether the mTOR signaling pathway can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…While it was crucial to maintain the morphological characteristics of mitochondria, our main object was to recover the energy homeostasis status of mitochondria as critical primary metabolic organelle by means of improving mitochondrial dynamics including mitochondrial proliferation, mitochondrial networks and mitophagy. 35 To evaluate energy homeostasis in nematode treated with FTP, we confirmed that FTP increased the expression of oxidative respiratory chainrelated genes from the mRNA level in nematode. Besides, the improvement endurance performance of nematode adapted to a greater reliance on FAO and ATP production (Fig.…”
Section: Disscussionmentioning
confidence: 62%
See 1 more Smart Citation
“…While it was crucial to maintain the morphological characteristics of mitochondria, our main object was to recover the energy homeostasis status of mitochondria as critical primary metabolic organelle by means of improving mitochondrial dynamics including mitochondrial proliferation, mitochondrial networks and mitophagy. 35 To evaluate energy homeostasis in nematode treated with FTP, we confirmed that FTP increased the expression of oxidative respiratory chainrelated genes from the mRNA level in nematode. Besides, the improvement endurance performance of nematode adapted to a greater reliance on FAO and ATP production (Fig.…”
Section: Disscussionmentioning
confidence: 62%
“…Based on the aforementioned experimental results, we found that FTP protected nematode mitochondria from high‐sugar‐diet injury by activating mitochondrial autophagy. While it was crucial to maintain the morphological characteristics of mitochondria, our main object was to recover the energy homeostasis status of mitochondria as critical primary metabolic organelle by means of improving mitochondrial dynamics including mitochondrial proliferation, mitochondrial networks and mitophagy 35 . To evaluate energy homeostasis in nematode treated with FTP, we confirmed that FTP increased the expression of oxidative respiratory chain‐related genes from the mRNA level in nematode.…”
Section: Disscussionmentioning
confidence: 64%
“…Chloroquine elicits detrimental effects on the mitochondria; conversely, rapamycin, a pharmacological inducer of autophagy (Sarkar et al 2009), can ameliorate mitochondrial diseases by restoring the autophagic flux and removing damaged mitochondria (Civiletto et al 2018;Li et al 2018). Rapamycin also upregulates the gene and protein expression of mitochondrial biogenesis, dynamics, and mitophagyrelevant markers, thereby preventing transition from brown to white adipocytes (Huwatibieke et al 2021). However, studies have yet to explore whether rapamycin can regulate mitochondrial bioenergetics and prevent metabolic dysregulations in an autophagy-dependent manner in adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In diabetes and obesity, excess insulin, branch chain amino acids, and ATP activate mTOR. This mTOR activation induces downregulation of mitochondrial biogenesis-and autophagy-related genes (50). Taken together, alteration in AMPK, SIRT1, and mTOR activity occur in energy surplus states such as obesity and type 2 diabetes to compensate for mitochondrial dysfunction and metabolic disorders.…”
Section: Energy Surplus Leads To Mitochondrial Dysfunction In Obesitymentioning
confidence: 98%
“…These mitochondrial dysfunctions are improved by lifestyle modifications such as physical exercise, calorie restriction, and weight loss, which are established strategies in the control of obesity, type 2 diabetes, and metabolic disorders (27). These practices induce activation of AMPK and SIRT1, while reducing mTOR activity at the molecular level (50). These molecular pathways provide a mechanism for the correction of mitochondrial dysfunction in the practices, suggesting that energy surplus is a major cause of mitochondrial dysfunction.…”
Section: Energy Surplus Leads To Mitochondrial Dysfunction In Obesitymentioning
confidence: 99%